Pengembangan Media Pembelajaran Topik Vektor Berbantuan 3D Aplication Scratch untuk Meningkatkan Hasil Belajar Siswa - Awaluddin Putri, Azzahra Aulia; Perdana, Riki (Edukimbiosis: Jurnal Pendidikan IPA, 2025)
This study aims to develop a Scratch 3D-based learning media on vector material that is deemed feasible based on the assessment results of validators. The development method used in this research is the 4D model (Define, Design, Develop, Disseminate). The data analysis technique employed was the calculation of average scores. The feasibility or validity test of the teaching module was conducted by five expert validators. The feasibility test results indicated scores of 95% for visual communication design, 95% for software engineering, 95% for the quality of learning media, and 100% for cognitive learning outcomes. Based on these results, the Scratch 3D-based learning media is declared feasible. This study concludes that the development of Scratch 3D-based learning media on vector material successfully meets the required criteria and can be utilized as an alternative learning medium for physics education in high schools.